Case report : a novel ASXL3 gene variant in a Sudanese boy - Ke Wu; Yan Cong (BMC, 2021)
Abstract Background Bainbridge-Ropers syndrome (BRPS) [OMIM#615485] is a neurodevelopmental disorder, characterized by delayed psychomotor development with generalized hypotonia, moderate to severe intellectual disability, poor or absent speech, feeding difficulties, growth failure, dysmorphic craniofacial features and minor skeletal features. The aim of this study was to investigate the genetic etiology of a Sudanese boy with severe developmental delay, intellectual disability, and craniofacial phenotype using trio-based whole-exome sequencing. To our knowledge, no patients with ASXL3 gene variant c.3043C>T have been reported detailedly in literature. Case presentation The patient (male, 3 years 6 months) was the first born of a healthy non-consanguineous couple originating from Sudan, treated for "psychomotor retardation" for more than 8 months in Yiwu. The patient exhibited severely delayed milestones in physiological and intellectual developmental stages, language impairment, poor eye-contact, lack of subtle motions of fingers, fear of claustrophobic space, hypotonia, clinodactyly, autistic features. Peripheral blood samples were collected from the patient and his parents. Trio-based whole-exome sequencing(Trio-WES) identified a de novo heterozygous ASXL3 gene variant c.3043C>T;p.Q1015X. Sanger sequencing verified variants of this family. Conclusion Trio-WES analysis identified a de novo nonsense variant (c.3043C>T) of ASXL3 gene in a Sudanese boy. To our knowledge, the patient with this variant has not been reported previously in literature. This study presents a new case for ASXL3 gene variants, which expanded the mutational and phenotypic spectrum.